التصميم الجيوديزي لشبكات المراقبة الارتفاعية في السدود "حالة دراسة سد الدويسات" - أحمد, محسن; فحصة, إياد (Latakia University Journal -Engineering Sciences Series, 2016)
يهدف البحث إلى دراسة الشبكة الارتفاعية لأحد السدود الحيوية في سوريا ، وتأمينه ضد مخاطر الفيضانات وبعد حدوث الهزات الأرضية ، بحيث تعطي القياسات الجيوديزية نتائج موثوقة ومضمونة ، يمكن الاعتماد عليها في اتخاذ القرارات اللاحقة، لما لها من تبعات اقتصادية وبشرية، سلباً كانت أم ايجاباً ، و لهذا الغرض تم التدرج في دراستنا لهذا البحث الخطوات المتعارف عليها وهي استطلاع المنطقة والكشف عن الحالة الراهنة للمنشأة المدروسة واقتراح شكل الشبكة الارتفاعية المحقق لشروط رياضية وهندسية تمت مناقشتها والحصول على أقضل النتائج خلال البحث الراهن، بعد ذلك وبشكل حقلي تم تنفيذ المقترحات النظرية مادياً وتجلى ذلك بإنجاز الشبكة المقترحة على أرض الواقع ومن بعد قياسها بأجهزة القياس الموصى بها ومعالجة النتائج مرحلياً ونهائياً وتقييم دقتها في كل مرحلة باستخدام الطرق الرياضية المناسبة ، ومناقشة النتائج واكتشاف الخلل الموجود في بنية المنشأة وإصلاحه ومن ثم التأكد عددياً وخلال فترة زمنية طويلة أن العمل تم تنفيذه بشكل آمن ولم تظهر أية مشاكل طارئة جديدة خلال فترة المراقبة ، وفي نهاية البحث تم اقتراح عدد من النتائج والتوصيات الهامة التي يجب الأخذ بها في هكذا نوع من المنشآت . The research aims to study the elevation network for important dam in Syria, and secured against flood risks and after the occurrence of earthquakes, to give reliable geodetic measurements and guaranteed results, which can be relied upon in subsequent decision-making, because of their economic and human consequences, negatively or positively, for this purpose our study had been gradual by applying customary steps by poll region and detection on the current status of the facility and suggesting proposal vertical control network form investigator mathematical and geometric conditions which are discussed to get best results during the current search, And then in the fields of theoretical proposals have been implemented and physically manifested completion of the proposed network on the ground and later have been measured with the recommended equipments and processing of the results to final progress and assess their accuracy at each stage using the appropriate mathematical methods, and discuss the results and discover the property's structure defects and then make sure numerically and over a long period of time that the work was carried out safely and no new emergency problems appear during the observation period. In the end of the research many of important results and recommendations were proposed, which must be introduced in such a kind of facilities.